Prediction of microvascular invasion of hepatocellular carcinoma with preoperative diffusion-weighted imaging: A comparison of mean and minimum apparent diffusion coefficient values. Issue 33 (August 2017) - Zhao, Jinkun; Li, Xubin; Zhang, Kun; Yin, Xiaoyu; Meng, Xiangfu; Han, Lizhu; Zhang, Xuening
Abstract : Abstract: The aim of the study was to investigate the value of preoperative diffusion-weighted imaging (DWI) in predicting microvascular invasion (MVI) of hepatocellular carcinoma (HCC), using and comparing mean and minimum apparent diffusion coefficient (ADC) values. Preoperative MR images of 318 patients with HCC confirmed by surgical pathology were retrospectively analyzed. All patients underwent preoperative DWI on a 1.5 Tesla MRI scanner. The mean and minimum ADC values of the tumors were measured. Interobserver agreements were assessed by the intraclass correlation coefficient (ICC). The ADC values were compared in HCCs between with and without MVI. ROC curves of ADC values were obtained and then compared in distinguishing HCCs with MVI from those without MVI. There were 211 HCCs with MVI and 107 HCCs without MVI. ICC for the measurements of the mean and minimum ADC values between both observers was 0.88 (95% CI 0.85 – 0.90) and 0.88 (95% CI 0.85 – 0.90), respectively. The mean and minimum ADC values of HCCs with MVI were lower than those of HCCs without MVI ( P = .00, .00, respectively). With a cut-off value of 0.98 × 10 –3 mm 2 /s, the minimum ADC (MinADC) showed a sensitivity of 62.56% and a specificity of 65.42% in predicting MVI, whereas the mean ADC provided a sensitivity of 79.15% and a specificity of 50.47% with a cut-off value of 1.19 × 10 –3 mm 2 /s. No significant difference existed between MinADC and mean ADC for their diagnostic performances in the prediction of MVI ( P = .48). DWI could preoperatively provide quantitative parameters for predicting MVI of HCC.